Efektivitas Penggunaan Whatsapp Group Oleh Siswa Sebagai Media Pembelajaran Jarak Jauh - Juniar, Dian; Sutarjo, Ajo; Hanif, Muhammad (Didaktika, 2022)
As is known, distance learning (PJJ) has been going on since the emergence of the COVID-19 pandemic in Indonesia. Among the various online learning platforms available, researchers are particularly interested in studying WhatsApp as a learning medium. MI Nurul Huda, Tangerang City, is one of the schools that has used WhatsApp media since the start of PJJ implementation. This study aims to (1) assess the effectiveness of WhatsApp Group as a distance learning medium for class V students, (2) identify the challenges students face when using WhatsApp Group as a learning medium, and (3) identify the strategies employed to overcome these challenges. Learn through a WhatsApp group. We used a qualitative research approach with case studies, utilizing questionnaires, interviews, and document studies as data collection techniques. This study found that the use of WhatsApp Group as a learning medium by fifth grade students at Madrasah Ibtidaiyah Nurul Huda, Tangerang City, was effective, as seen from the results of student questionnaires with an average score (SB) of Very Good. The average value of student report cards has increased both before and after using the WhatsApp Group application as a learning medium. Students face obstacles such as a lack of understanding of their duties and quota barriers, which can lead to undersatisfaction. In the meantime, the teacher is making efforts to communicate with the parents of the students, promote the Internet assistance quota from the ministry, and acknowledge or understand students who have cell phone restrictions by providing them with extended time limits for task completion.